Desenvolvimento de sistema híbrido PSA/TSA aplicável à separação de hidrogênio de produtos da reforma a vapor - Alves, Jean Faber Araújo (2016)
The hydrogen has been showed as a promising alternative in the world energetic scenario.Considered like a clean combustion fuel, for doesn’t produce particulates and carbon oxides, its use fits to requirements of nowadays context that the planet faces. One of the way to produce hydrogen is by thermochemical conversions, Steam reforming of Hydrocarbons or biomass gasification. However, the product’s current that is generated presents in its composition, in addition to hydrogen, species that causes potentially negative environmental impacts. Between technologies applied to the hydrogen separation from these products are the cyclic processes of separation by adsorption. For this motive was developed a hybrid system of separation by adsorption, that permits the study of PSA/TSA cyclic steps, in a bed filled with activated carbon WV1050 and percolated by a syngas equimolar mixture. The adsorption equilibrium was evaluated by the gravimetric technique, obtaining the adsorption isotherms, and kinetic was approached by LDF model. Simulations were developed to produce breakthrough curves that permitted the determination of theoretical bed capacity. Was used a classical mathematic model and the simulations were made in gPROMS® environment (Process System Enterprise, London, UK). Was experimentally verified, in tested conditions, the fast bed saturation when it was pressurized with the feed mixture (syngas). The adsorption equilibrium of booth species on WV1050 could be described by the Langmuir Model and the heat of adsorption could be calculated by the Van’t Hoff equation. The theoretical bed capacity, for the CO adsorbed quantity, obtained by simulation was compared with the adsorbed quantity that the experimental isotherm showed, in the same pressure and temperature of 30ºC. For pressures of 3,5 and 5 bar, was verified that the model provided a slightly higher value that the showed by the isotherm.